2005
DOI: 10.1097/01.sle.0000166967.49274.ca
|View full text |Cite
|
Sign up to set email alerts
|

Complete Evidence Regarding Major Vascular Injuries During Laparoscopic Access

Abstract: Recent reports by the Australian Safety and Efficacy Register for New interventions and Procedures (ASERNIP-S) and the Royal Australian and New Zealand College of Obstetricians and Gynaecologists (RANZCOG) concluded that insufficient evidence is available to assess the safety of the open versus closed laparoscopy in regard to major vascular and visceral injuries. The aim of this study was to assess the relative safety of open and closed laparoscopy with respect to rates of major vascular and visceral injuries.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
1
35

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 10 publications
1
49
1
35
Order By: Relevance
“…Çalışmamızda vasküler yaralanma oluşmadı. Başka bir çalışmada her ne kadar durum istatistiksel olarak anlamlı değer-lere ulaşmasa da kapalı giriş tekniğinde vasküler yaralanma açık girişe göre daha fazla oranda tespit edilmiştir (13). Bu konuda literatürde karşıt çalışmalar da mevcuttur.…”
Section: Discussionunclassified
“…Çalışmamızda vasküler yaralanma oluşmadı. Başka bir çalışmada her ne kadar durum istatistiksel olarak anlamlı değer-lere ulaşmasa da kapalı giriş tekniğinde vasküler yaralanma açık girişe göre daha fazla oranda tespit edilmiştir (13). Bu konuda literatürde karşıt çalışmalar da mevcuttur.…”
Section: Discussionunclassified
“…1). Based on a literature review, Larabina and Nottle estimated that a major vascular injury occurred, on average, every 2,272 procedures, and a visceral injury every 1,381 procedures [4]. van der Voort and colleagues reported that 42% of bowel injuries were from insertion of the trocar and 26% from electrosurgery with an overall mortality rate of 3.6% [5].…”
Section: Safety Problems With Minimally Invasive Surgerymentioning
confidence: 98%
“…Despite the extremely low incidence of serious complications, 2 separate meta-analyses have demonstrated statistically higher rates of vascular and bowel injury with closed versus open laparoscopy. 29,30 The fact that more than 35% of general surgeons selectively use the Veress needle in their practices indicates some variance with regards to laparoscopic access capabilities and choice. Survey respondents also clearly described their preference for a periumbilical primary entry location.…”
Section: Discussionmentioning
confidence: 99%